Skin Cancer in Puerto Rico: a Multiannual Incidence Comparative Study - De La Torre-Lugo, Eneida M.; Figueroa, Luz D.; Sánchez, Jorge L.; Morales-Burgos, Adisbeth; Conde, Daniel (Puerto Rico Health Sciences Journal, 2010)
Background: The incidence of skin cancer continues to increase worldwide. The purpose of this study was to determine the incidence of skin cancer in Puerto Rico in a selected year (2005) and to compare these findings with those previously reported for Puerto Rico in 1974 and 1981 and with other countries. Methods: The data was collected from the pathology reports corresponding to the period of January to December 2005 of 21 participating Pathology Laboratories throughout Puerto Rico. The rate and distribution of the main types of skin cancer was calculated based on sex, age, anatomic location and laterality. Results: The incidence of skin cancer in Puerto Rico for 2005 was 6,568 cases, which represent a rate of 167.9 per 100,000 inhabitants. The most common type of skin cancer was basal-cell carcinoma. Skin cancer was more common in males except for melanoma, which was more common in females. The incidence increases with age on all types of skin cancer. The head and neck area was the most frequent location, except for melanoma in women, which was more common on the legs. The incidence rate was 41.5/100,000 in 1974, 52.5/100,000 in 1981 and 167.9/100,000 in 2005, a 305% increase. Conclusions: We found an increasing incidence of skin cancer in Puerto Rico when compared with previous reported data. This analysis provides a comprehensive evaluation of the epidemiology of skin cancer in Puerto Rico.